Novel fouling resistant magnetically-responsive membranes for treatment of impaired water - Himstedt, Heath Henry, author; Wickramasinghe, S. Ranil, advisor; Bailey, Travis, committee member; Qian, Xianghong, committee member; Ulbricht, Mathias, committee member; Waskom, Reagan, committee member (Colorado State University. Libraries, 2012)
The focus of this dissertation research is the development of novel fouling resistant magnetically-responsive micromixing filtration membranes. Maintenance and replacement costs account for well over half the total cost of membrane processes. Fouling limits membrane performance by reducing membrane flux and lifetime. Specialized stimuli-responsive membranes have been investigated as a means to combat fouling; however, stimuli such as pH, solution ionic strength, and temperature require changes to the entire feedstream to impart a response. This is time consuming and expensive. The novel membranes presented in this dissertation combat fouling through active hydrodynamic disruption of the filtration boundary layer via instant activation by an external magnetic field without the need to adjust feedstream conditions. The fouling resistant properties of these membranes were tested by using them to treat oily wastewaters from oil and gas production, known as produced water. Chapter 1 introduces concepts referenced throughout the dissertation narrative including basic principles of pressure-driven membrane technology; the principles of membrane fouling and fouling resistant membranes; a review of applications of (super)paramagnetic nanoparticles; and a discussion of produced water and the treatment challenges it presents. Chapters 2 through 6 are published, or soon to be submitted, scientific papers which chronicle the development and application of these novel membranes. Chapter 2 discusses the concepts behind magnetically-activated micromixing and presents initial proof-of-concept nanofiltraiton membranes. Chapter 3 employs track-etched membranes to characterize the modification protocol and the magnitude of the magnetic response, as well as the relationship between the two. Chapter 4 determines the effect of modification grafting density on mixing efficacy and membrane filtration properties. Chapter 5 shows the improvements to membrane performance and lifetime attributable to magnetically-activated mixing during filtration of model produced water and realistic produced water. Chapter 6 builds upon Chapter 5 by using treated realistic produced water permeate as irrigation water. Chapters 7 and 8 summarize the research findings and present possible direction for future research, respectively. This work presents the development and one potential application of novel magnetically-activated micromixing membranes. These membranes reduce membrane fouling by inducing hydrodynamic mixing in an alternating magnetic field. These membranes could lead to improved membrane performance and lifetime when treating highly fouling feedstreams. This would significantly decrease membrane maintenance and replacement costs and could lead to new clean water product streams.
Keywords: impaired water; water treatment; responsive membranes; magnetic response; micromixing; fouling resistant